The mRNA component of LNP-mRNA vaccines triggers IFNAR-dependent immune activation which attenuates the adaptive immune response - Bar-On, Liat; Cohen, Hila; Elia, Uri; Cherry-Mimran, Lilach; Cohen, Ofer; Erez, Noam (Frontiers in Immunology, 2025)
Encapsulation of mRNA in lipid nanoparticles (LNPs) has established the LNP–mRNA platform as the strategy of choice for the rapid development of vaccines against both existing and emerging pathogens. However, despite its widespread global implementation during the COVID-19 pandemic, the immunological mechanisms underlying its efficacy remain incompletely understood. In this study, we investigated in a murine model, the early and robust innate immunity events elicited following immunization with an LNP–mRNA vaccine. Using mRNAs encoding two different proteins as well as a non-coding sequence, it is demonstrated that the mRNA component—rather than the LNP or the encoded antigen —is essential for inducing a potent innate immune response. This response is characterized by rapid activation of dendritic cells, recruitment of monocytes to draining lymph nodes, and systemic cytokine responses involving activation of various innate immune cell populations. Notably, these effects are all dependent on signaling through the type I interferon receptor (IFNAR). Importantly, we show that even a brief and transient inhibition of IFNAR signaling significantly enhances the ability of the LNP–mRNA vaccine to elicit adaptive immune responses, as evidenced by increased frequencies of antigen-specific CD8+ T cells and elevated titers of antigen-specific antibodies. Together, our findings reveal that the strong IFNAR-dependent innate response induced by mRNA can attenuate subsequent adaptive immunity. These insights should be considered in the future design and optimization of LNP–mRNA vaccine platforms.